Three eriophyoid mite species (Acari: Eriophyoidea: Eriophyidae) from Iran - Xue, Xiao-Feng; Sadeghi, Hussein; Honarmand, Arash (Zootaxa, 2016)
Three mite species of the family Eriophyidae from Iran are described and illustrated. They are: Tegolophus marrubiumer sp. nov. on Marrubium vulgare L. (Lamiaceae); Phyllocoptes sp. cf. balasi Farkas, 1962 on Sanguisorba minor Scop. subsp. minor (Rosaceae) and Aceria fasciculifolis sp. nov. on Astragalus fasciculifolius Boiss. (Fabaceae). Both new species described herein are vagrants on their respective host plants.